Adjunctive lithium treatment in the prevention of suicidal behavior in patients with depression and comorbid personality disorders. (October 2014) - Rombold, Felicitas; Lauterbach, Eric; Felber, Werner; Mueller-Oerlinghausen, Bruno; Ahrens, Bernd; Bronisch, Thomas; Kilb, Birgit; Lewitzka, Ute; Richter, Kneginja; Broocks, Andreas; Heuser, Isabella; Hohagen, Fritz; et al.
Abstract Objective. Patients with both major depression and personality disorders have a high risk of suicidal behavior. Lithium is meant to have anti-suicidal properties in patients with affective disorders. The anti-suicidal effect of lithium in patients with affective disorders and comorbid personality disorders has not been investigated yet. Methods. A post-hoc analysis of a subsample of patients with depression and comorbid personality disorder (PD) and a recent suicide attempt (n = 19) from the prospective, placebo-controlled lithium intervention study (N = 167), was conducted. Results. Three patients in the lithium group (n = 8) and two patients in the placebo group (n = 11) presented a suicide attempt throughout the course of the study. No differences related to suicidal behavior could be detected between the placebo group and the group with lithium intervention. Conclusions. On the basis of the small sample size, among patients with comorbid PD, lithium does not seem to have an effect on suicidal behavior in contrast to patients with affective disorders without comorbid PD.